Metacognitive beliefs, environmental demands and subjective stress states: A moderation analysis in a French sample. (October 2016) - Trouillet, Raphaël; Doron, Julie; Combes, Romain
Abstract: Subjective stress states elicited in the context of performance are composed of three broad syndromes as measured by the Short Stress State Questionnaire (SSSQ): Task-engagement, Worry and Distress (Helton, 2004). They are supposed to emerge from the interplay between environmental demands and metacognitive beliefs, but this assumption remains untested. Our research addressed this issue and tested the hypothesis that subjective stress states syndromes may be explained by environmental demands, metacognitive beliefs and their interplay. We recruited 210 participants who completed a working memory, vigilance or magazine-reading task. Our main results revealed that each syndrome of stress is explained by a specific set of predictors: Distress is explained by the dynamic between metacognition and environmental demands, Worry was only predicted by metacognition and Task engagement is explained by both environmental demands and metacognition. Our results were discussed in reference to the S-REF model (Wells & Matthews, 1994) and they brought some insight in when environmental and metacognitive factors predict stress state components in performance settings. Highlights: The French SSSQ provides a reliable and valid measure of stress states syndromes. The Worry syndrome is unaffected by environmental demands. Environmental and metacognitive factors contribute to the Task Engagement syndrome. Metacognition moderates the effect of environmental demands on the distress syndrome.